Eyebrows, Rajesh Mansion - Ghosh, Ayan (Jio Institute, 2023)
The cantilevered ledge located above windows is referred to as eyebrows. Their main purpose is to block direct sunlight and shade the interiors. By using clusters of eyebrows, architects used them to accentuate the rhythmic horizontality of buildings, including at Rajesh Mansion.